Influenza‐induced, helper‐independent CD8+ T cell responses use CD40 costimulation at the late phase of the primary response. Issue 1 (1st January 2013) - Seah, Shirley G. K.; Brady, Jamie L.; Carrington, Emma M.; Ng, Wy Ching; Sutherland, Robyn M.; Hancock, Manuela S.; La Gruta, Nicole L.; Brown, Lorena E.; Turner, Stephen J.; Lew, Andrew M.; Zhan, Yifan
Abstract : Direct costimulation of CD8 + T cells is more important than the canonical licensing of DCs by CD4 help, in influenza. Abstract : The helper‐dependent pathway of priming CD8 + T cells involves "licensing" of DCs by CD40L on CD4 + T cells. The helper‐independent ("helpless") pathways elicited by many viruses, including influenza, are less widely understood. We have postulated that CD40L can be up‐regulated on DCs by such viruses, and this promotes priming of CD8 + T cells via CD40. Most studies on costimulation have been performed in the presence of CD4 + T cells, and so the role of CD40L costimulation under helpless circumstances has not been fully elucidated. Here, we investigated such a role for CD40L using CD40L KO mice. Although the number of influenza‐specific CD8 + T cells was unaffected by the absence of CD4 + T cells, it was markedly decreased in the absence of CD40L. Proliferation (the number of CD44 + BrdU + influenza‐specific CD8 + T cells) in the primary response was diminished in CD40L KO mice at Day 8 but not at Day 5 after infection. MLR studies indicated that CD40L expression on DCs was critical for CD8 + T cell activation. Adoptive transfer of CD40 KO CD8 + T cells compared with WT cells confirmed that CD40 on such cells was critical for the generation of primary anti‐influenza CD8 + T cell responses. The late effect also corresponded with the late expression of CD40 by influenza‐specific CD8 + T cells. We suggest that costimulation via CD40L on DCs and CD40 on CD8 + T cells is important in optimizing primary CD8 + T cell responses during influenza infection.